Modeling the behavior of Listeria innocua in Italian salami during the production and high-pressure validation of processes for exportation to the U.S. (February 2021) - Bonilauri, Paolo; Merialdi, Giuseppe; Ramini, Mattia; Bardasi, Lia; Taddei, Roberta; Grisenti, Maria Silvia; Daminelli, Paolo; Cosciani-Cunico, Elena; Dalzini, Elena; Frustoli, Maria Angela; Giacometti, Federica; Tomasello, Federico; et al.
Abstract: A model describing Listeria innocua evolution according to process parameters of 51 Italian salami processes and HPP in 31 companies was developed. A total of 51 challenge tests were performed. During processing a L. innocua reduction of 0.34–4.32 Log10 CFU/g was observed and HPP further reduced the count of 0.48–3.47 Log10 CFU/g; an overall reduction of 1.04–5.68 is reached. PH after acidification/drying process, aw after seasoning, duration of the seasoning and caliber resulted associated ( p < 0.05) with L. innocua decrease. HPP efficacy was associated (p < 0.05) with a w and pH of the product: higher the pH and a w after the acidification/drying and seasoning phases, higher resulted the L. innocua reduction after HPP. No significant association was observed between L. innocua and salt, nitrate and starter content and other characteristics of process. The model meets companies and Authorities needs and represents a useful tool to predict L. monocytogenes lethality, giving recommendations to food business operators interested in exportation to the U.S.